2014
DOI: 10.1186/1471-2474-15-426
|View full text |Cite
|
Sign up to set email alerts
|

Joint motion quality in vibroacoustic signal analysis for patients with patellofemoral joint disorders

Abstract: BackgroundChondromalacia, lateral patellar compression syndrome and osteoarthritis are common patellofemoral joint disorders leading to functional and/or structural disturbances in articular surfaces. The objective of the study was to evaluate their impact on joint motion quality via the vibroacoustic signal generated during joint movement analysis.MethodsSeventy-three patients (30 with chondromalacia, 21 with lateral patellar compression syndrome, and 22 with osteoarthritis) and 32 healthy controls were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 33 publications
0
52
0
Order By: Relevance
“…VAG is a technique based on accurate recording of vibroacoustic signals generated by relative movement of articular cartilage surfaces. It is known that cartilage pathology may change vibroacoustic signals, and differences between normal and abnormal joints are observed [14‐17]. This phenomenon also is detected for CMP, which generates the most prominent vibrations [14,18].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…VAG is a technique based on accurate recording of vibroacoustic signals generated by relative movement of articular cartilage surfaces. It is known that cartilage pathology may change vibroacoustic signals, and differences between normal and abnormal joints are observed [14‐17]. This phenomenon also is detected for CMP, which generates the most prominent vibrations [14,18].…”
Section: Introductionmentioning
confidence: 81%
“…Hence, the authors suggest a role for more sensitive and responsive diagnostic techniques in the assessment of mild and moderate disorders. One of these methods for direct analysis of crepitations could be vibroarthrography (VAG), which seems to support physical examination for objective assessment of quality of joint motion [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…34,35 In addition, wearable motion sensors have also been used to assess joint stability tests such as assessment of ACL insufficiency by measuring rotational rate and peak accelerations with an IMU applied in the Pivot Shift test. 36 Furthermore, IMUs have been applied to measure shoulder joint function before and after orthopaedic interventions.…”
Section: Physical Functionmentioning
confidence: 99%
“…Both variability (VMS) and amplitude (R4) of representative signals are characterized by low values. Especially the low values of the R4 parameter that indicate a lack of repetitive large peaks, whose presence often corresponds with macroscopic joint cartilage abnormalities or signi cant maltracking of articular surfaces [18,37]. In turn, low spectral activity analyzed by summing spectral power of the VAG signal in two bands: 50-250 Hz (P1) and 250-450 Hz (P2) seems to be related with intact integrity of the super cial layer of hyaline cartilage and an e cient lubrication mechanism [36,44].…”
Section: Discussionmentioning
confidence: 99%
“…The short-time spectra were obtained by computing the discrete Fourier transform of segments, 150 samples each, Hanning window, and 100 samples overlap of each segment. The spectral activity was analyzed by summing spectral power of the VAG signal in two bands: 50-250 Hz (P1) and 250-450 Hz (P2) [18,[36][37][38][39]. The performed ANOVA revealed that there was a signi cant main effect of the applied load on values of each analyzed parameter, similar in both lower limbs.…”
Section: Assessment Of Arthrokinematic Motion Qualitymentioning
confidence: 99%